Direct Ink Writing 3D Printing of Graphene/Al2O3 Composite Ceramics with Gradient Mechanics. Issue 8 (17th March 2023) - Fan, Jiang; Guan, Ruihua; Ou, Kangtai; Fu, Qiang; Liu, Qingxiao; Li, Dian-sen; Zheng, Hengyu; Sun, Youyi
Abstract : A new graphene (G)/Al2 O3 composite ceramic with tunable mechanics is prepared by direct ink writing (DIW) 3D‐printing technology. It is found that the bending strength, fracture toughness, and hardness all increase with increasing in content of G. The bending strength, fracture toughness, and hardness of G/Al2 O3 composite ceramic (4.0 wt‰) are improved to be 45.0%, 40.6%, and 21.9% comparing to Al2 O3 ceramic, respectively. The result is attributed to good reinforcement of G and inhibition of Al2 O3 phase growth by G. Furthermore, the gear wheel with gradient mechanics is also designed and fabricated by the DIW 3D‐printing technology from various G/Al2 O3 composite gels. It exhibits excellent wear resistance and low generation of heat during rotational friction. Herein, a new method is provided to fabricate G‐based ceramics with gradient structure and mechanics for various applications. Abstract : A new direct ink writing (DIW) 3D‐printing process is developed to prepare graphene/Al2 O3 composite ceramics with controllable mechanical properties. In addition, composite ceramics can be applied to gradient mechanical gears. Because of the low heat generated by friction, it shows excellent wear resistance and thermal stability. Herein, a new method is opened up for designing and preparing Al2 O3 ‐based ceramics with gradient structure.